2019
DOI: 10.3389/fpsyg.2019.02798
|View full text |Cite
|
Sign up to set email alerts
|

Religious Affiliation and Marital Satisfaction: Commonalities Among Christians, Muslims, and Atheists

Abstract: Scientists have long been interested in the relationship between religion and numerous aspects of people's lives, such as marriage. This is because religion may differently influence one's level of happiness. Some studies have suggested that Christians have greater marital satisfaction, while others have found evidence that Muslims are more satisfied. Additionally, less-religious people have shown the least marital satisfaction. In the present study, we examined marital satisfaction among both sexes, and among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 71 publications
2
7
0
Order By: Relevance
“…Interestingly, the authors investigated the cortisol levels (a hormone that is often associated with stress) of married and single persons, and found that married individuals had lower cortisol levels than unmarried and previously married people, which would suggest that they experience lower levels of stress. Similar patterns have been observed among persons in intimate relationships (not necessarily married), who exhibited lower levels of stress compared with single persons when stress was assessed by blood pressure (Sisca, 1985), self-reported measures (Hudson & O'Regan, 1994), or a broad range of well-being indices (Sorokowski et al, 2019).…”
Section: Intimate Relationshipssupporting
confidence: 56%
“…Interestingly, the authors investigated the cortisol levels (a hormone that is often associated with stress) of married and single persons, and found that married individuals had lower cortisol levels than unmarried and previously married people, which would suggest that they experience lower levels of stress. Similar patterns have been observed among persons in intimate relationships (not necessarily married), who exhibited lower levels of stress compared with single persons when stress was assessed by blood pressure (Sisca, 1985), self-reported measures (Hudson & O'Regan, 1994), or a broad range of well-being indices (Sorokowski et al, 2019).…”
Section: Intimate Relationshipssupporting
confidence: 56%
“…Data for the study was obtained from the published dataset [50], which include 7178 married individuals from 33 countries and territories: Brazil, Bulgaria, Canada, China, Croatia, Estonia, Germany, Ghana, Greece, Hong Kong, Hungary, India, Indonesia, Iran, Italy, Kazakhstan, Kenya, Malaysia, Mexico, Nigeria, Pakistan, Poland, Portugal, Romania, Russia, Saudi Arabia, Slovakia, South Korea, Spain, Switzerland, Turkey, United Kingdom, and Uganda. The data was collected in 2012 and 2013 and was part of a broad cross-cultural research project, which investigated, inter alia, romantic relationships [48,[51][52][53][54], behaviors [55], and their motives [56] across numerous countries and territories. All samples were convenience samples (e.g., students, acquaintances of the researchers, participants of vocational courses, inhabitants of home towns of the researchers etc.).…”
Section: Participantsmentioning
confidence: 99%
“…In this context, education may be considered not only an obligation to invest in one’s own needs, career or childrearing, but also as a supportive resource, which gives tools or opens new possibilities. Moreover, even though previous studies provided evidence that marital satisfaction may not be related to religious affiliation, i.e., that Christians, Muslims, and atheists report the same levels of marital satisfaction [ 48 ], some researchers hypothesized that it may be rather the intensity of religiousness that affects the spouse satisfaction and parenthood [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Participants first gave informed consent. They then filled out a set of questionnaires, including the TLS-45 (Sorokowski et al, 2021), marital satisfaction (Kowal et al, 2021;Sorokowski et al, 2019), mate preferences (Walter et al, 2020), and social media (Kowal et al, 2020). For more details on sampling and procedure, see Sorokowski et al (2021).…”
Section: Methodsmentioning
confidence: 99%
“…An exemplary item from the scale reads, "How satisfied are you with your relationship?". The KANSAS scale has been used in many cross-cultural studies, as it exhibits good psychometric properties (see, e.g., Sorokowski et al, 2019).…”
Section: Instrumentsmentioning
confidence: 99%